Efektifitas Tindakan Talk Down Terhadap Perilaku Kekerasan Pada Pasien Skizofrenia di Ruang Unit Pelayanan Intensif Psikiatri Rumah Sakit Jiwa Mutiara Sukma Provinsi NTB - Joni Aswandi; Mega Sara Yulianti; Dea Nadia (Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
Schizophrenia is a psychotic condition that affects individual functioning characterized by disorganized thinking, delusions, hallucinations, and maladaptive behavior. Common symptoms of schizophrenia include excessive behavioral changes such as sudden anger, screaming, and even violent behavior. The risk of violent behavior indicates the ability to harm oneself, others, and the environment. In Indonesia, the risk of violent behavior is 0.8% out of 10,000 people. With such a high rate, if left untreated, it can lead to harmful consequences such as self-injury, harm to others, and harm to the environment. Therefore, there is a need for new method or approach to prevent and reduce agitation and aggressiveness in violent behavior and to increase feelings of being cared for, respected, and honored, namely through Talk Down intervention. This study aimed to determine the effectiveness of Talk Down intervention on violent behavior in schizophrenia patients. The research design was quasi-experimental with an experimental approach using pre- post-test with a control group, with a sample size of 70 respondents selected through purposive sampling. Data were collected through questionnaires using interview and observation techniques. The results of the study showed that in the treatment group, before Talk Down intervention, the mean score was 18.26, and after Talk Down, it was 5.20. In the control group, before intervention, the mean score was 18.67, and after, it was 13.8. The Mann-Whitney U test calculation yielded an Asymp. Sig. (2-tailed) of 0.000 < 0.05. It can be concluded that Talk Down intervention is effective in reducing signs of violent behavior symptoms in schizophrenia patients in the UPIP ward of Mutiara Sukma Mental Hospital, NTB Province. It is hoped that Talk Down can be used as a nursing therapy for violent behavior patients.